Combatting Child Marriage - Tagorda, Yasmin Abdurahim (Advanced Studies on Socio-Economy Development, 2024)
Numerous initiatives, including one in the Philippines, have been developed around the world to support the demand to end child marriage. Child marriage is widely practiced in indigenous and Muslim communities in the Philippines, but Republic Act No. 11596, known as the